Adult mental health outcomes of adolescent depression: A systematic review - Johnson, Dylan; Dupuis, Gabrielle; Piche, Justin; Clayborne, Zahra; Colman, Ian (Depression and anxiety, 2018)
Background Adolescent depression may increase risk for poor mental health outcomes in adulthood. The objective of this study was to systematically review the literature on the association between adolescent depression and adult anxiety and depressive disorders as well as suicidality. Methods EMBASE, MEDLINE, and PSYCinfo databases were searched and longitudinal cohort studies in which depression was measured in adolescence (age 10–19) and outcomes of depressive disorders, anxiety disorders, or suicidality were measured in adulthood (age 21+), were selected. Meta‐analysis using inverse variance and random effects modeling, along with sensitivity analyses, were used to synthesize article estimates. Results Twenty articles were identified, representing 15 unique cohorts. Seventeen of 18 articles showed adolescent depression increased risk for adult depression; eleven pooled cohorts estimated that adolescents with depression had 2.78 (1.97, 3.93) times increased odds of depression in adulthood. Seven of eight articles that investigated the association between adolescent depression and any adult anxiety found a significant association. Three of five articles showed a significant association between adolescent depression and adult suicidality. Conclusion This review shows that adolescent depression increases the risk for subsequent depression later in life. Articles consistently found that adolescent depression increases the risk for anxiety disorders in adulthood, but evidence was mixed on whether or not a significant association existed between adolescent depression and suicidality in adulthood. Early intervention in adolescent depression may reduce long‐term burden of disease.